Content analysis as a methodology in Qualis-CAPES A1 journals in Science Education (Research, Society and Development, 2021)
The research methodology explains the path taken in a study. In this sense, we researched the analysis methodologies used in 677 articles, from two Qualis-CAPES A1 journals, in order to identify the use of Content Analysis. The investigated magazines were “Essay: Research in Science Education” and “Science and Education”, with 145 articles presenting the descriptor “content analysis”. From these articles, we analyzed the mention of the descriptor for the first time in the text (title, abstract or keywords). Thus, by employing content analysis, we achieved at two categories: "the mapping of Content Analysis in research in science education" and the emerging category "the rigor of the theoretical framework in the methodological path of research". In one sense, we observed that, the content analysis was mentioned for the first time in the development of the work in 61.4% of the articles. And as a reference for this analysis methodology, Laurence Bardin was mentioned in 76.1% of the analyzed articles.